1996
DOI: 10.1128/mcb.16.3.1203
|View full text |Cite
|
Sign up to set email alerts
|

The Recessive Phenotype Displayed by a Dominant Negative Microphthalmia-Associated Transcription Factor Mutant Is a Result of Impaired Nuclear Localization Potential

Abstract: In cotransfection assay, a strong dominant negative effect of Mi wh -MITF against wild-type MITF-dependent transactivation system on tyrosinase promoter was observed, but mi-MITF had a small effect. However, by the conjugation of simian virus 40 large-T-antigen-derived nuclear localization signal to mi-MITF, the dominant negative effect was enhanced. Furthermore, we demonstrated that the interaction between wild-type MITF and mi-MITF occurred in the cytoplasm and that mi-MITF had an inhibitory effect on nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 53 publications
(59 reference statements)
5
83
1
Order By: Relevance
“…One approach was the use of cotransfection assays and in vitro DNA binding assays, whereas the other approach utilized the available mouse models that harbor different genetic mutations in MITF. In 1996, Kitamura and his colleagues (6) demonstrated that the MITF protein in mi/mi mice is mainly located in the cytoplasm, and therefore they proposed that the presence of the mutated protein can lead to cellular defect by anchoring MITF hetrodimerization partners in the cytoplasm. MITF regulates the expression of mouse mast cell protease (mMCP)-6 (7), mMCP-5 (8) c-kit (9), p75 nerve growth factor (8), granzyme B (10), tryptophan hydroxylase (11), and cathepsin K (12).…”
Section: The Microphthalmia Transcription Factor (Mitf)mentioning
confidence: 99%
“…One approach was the use of cotransfection assays and in vitro DNA binding assays, whereas the other approach utilized the available mouse models that harbor different genetic mutations in MITF. In 1996, Kitamura and his colleagues (6) demonstrated that the MITF protein in mi/mi mice is mainly located in the cytoplasm, and therefore they proposed that the presence of the mutated protein can lead to cellular defect by anchoring MITF hetrodimerization partners in the cytoplasm. MITF regulates the expression of mouse mast cell protease (mMCP)-6 (7), mMCP-5 (8) c-kit (9), p75 nerve growth factor (8), granzyme B (10), tryptophan hydroxylase (11), and cathepsin K (12).…”
Section: The Microphthalmia Transcription Factor (Mitf)mentioning
confidence: 99%
“…39,40 A retroviral vector, pM5Gneo, 41 a derivative of myeloproliferative sarcoma virus vector, was a kind gift from Dr. W. Ostertag (Universitä t Hamburg, Hamburg, Germany). The purified SmaI-HincII fragment from pBS-ϩ-MITF or pBS-mi-MITF was introduced into the blunted EcoRI site of pM5Gneo.…”
Section: Construction Of Retrovirus Vector and Its Infectionmentioning
confidence: 99%
“…39,40 Oligonucleotides were labeled with ␣-[ 32 P]dCTP by filling 5Ј-overhangs, and were used as probes for EGMSA. DNA binding assays were performed in a 20 l reaction mixture containing 10 mmol/L Tris-HCl (pH 8.0), 1 mmol/L ethylenediaminetetraacetic acid, 75 mmol/L KCl, 1 mmol/L dithiothreitol, 4% Ficoll type 400, 50 ng poly (dI-dC), 25 ng of the labeled DNA probe, and 3.5 g of GST-ϩ-MITF or GST-mi-MITF fusion protein.…”
Section: Electrophoretic Gel Mobility Shift Assay (Egmsa)mentioning
confidence: 99%
“…The MITF encoded by the mutant mi allele deletes 1 of 4 consecutive arginines in the basic domain (hereafter mi-MITF) (Hodgkinson et al, 1993;Hemesath et al, 1994;Steingrimsson et al, 1994). The mi-MITF is defective in the DNA binding activity and the nuclear localization potential, and it does not transactivate target genes Takebayashi et al, 1996;Tsujimura et al, 1996;Jippo et al, 1997;Ito et al, 1998;Kim et al, 1998). The mi/mi mice show microphthalmia, depletion of pigment in both hair and eyes, osteopetrosis, and decrease of mast cells (Silvers, 1979;Green, 1981;Stevens and Loutit, 1982;Stechschulte et al, 1987).…”
Section: Introductionmentioning
confidence: 99%